2014
DOI: 10.1097/scs.0000000000000767
|View full text |Cite
|
Sign up to set email alerts
|

The Thickness of Alveolar Bone at the Mandibular Canine and Premolar Teeth in Normal Occlusion

Abstract: This study presented the thickness of the buccal and lingual bone in different locations apical to the CEJ in subjects with normal occlusion and the frequency distribution of thick buccal bone wall (≥ 2 mm). The second premolar had the highest frequency distribution of thick buccal bone (≥ 2 mm) when compared with canine and the first premolar. The teeth with thin buccal bone (< 2 mm) should be treated with care for the implant because a thin buccal bone may be damaged more easily and buccal bone resorption ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Other studies analyzing patients of different ages did not show any difference in BBT [ 37 , 47 ]. Neither could BBT be shown to vary by the location of measurement [ 37 , 49 ] or by the patients’ ethnicity or sex [ 47 ]. The latter is generally not believed to be associated with the BBT [ 38 , 47 , 49 , 63 , 115 , 135 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies analyzing patients of different ages did not show any difference in BBT [ 37 , 47 ]. Neither could BBT be shown to vary by the location of measurement [ 37 , 49 ] or by the patients’ ethnicity or sex [ 47 ]. The latter is generally not believed to be associated with the BBT [ 38 , 47 , 49 , 63 , 115 , 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neither could BBT be shown to vary by the location of measurement [ 37 , 49 ] or by the patients’ ethnicity or sex [ 47 ]. The latter is generally not believed to be associated with the BBT [ 38 , 47 , 49 , 63 , 115 , 135 ]. On the contrary, some studies show statistically significant associations between the BBT and age or sex, even if in just some sites [ 56 , 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the reference point seems important for evaluating the labial and palatal bony wall thickness [12]. The labial bone crest was considered a reference point in some cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…The previous report showed that alveolar thickness of the central incisor was greater and that the palatal cortex of the central incisor was higher than the lateral incisors in individuals, irrespective of having a long face or short face [10]. Limited information was available for the alveolar bony wall thickness with normal occlusion, and results were gathered from the maxillary and mandibular canine and premolar regions [11,12]. This study investigated the labial and palatal bony wall thickness of the maxillary central and lateral incisors using CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…The permanent maxillary canines play a key role in shaping dentition and maintaining its function, and their presence in the dental arch is crucial for a balanced dynamic occlusion and for facial esthetics and harmony. 13 - 15 Thus, a great deal of effort should be expended to maintain or to avoid the extraction of an impacted permanent maxillary canine 16 - 18 . The present clinical case illustrates very well this scenario, with two impacted maxillary canines, one buccally inclined and one palatally inclined, which were moved into the spaces created orthodontically.…”
Section: Discussionmentioning
confidence: 99%